The course of problematic social media use in young adolescents: A latent class growth analysis. Issue 2 (15th November 2021) - Boer, Maartje; Stevens, Gonneke W. J. M.; Finkenauer, Catrin; van den Eijnden, Regina J. J. M.
Abstract: Using four waves of longitudinal data collected in 2015–2019 from 1419 Dutch adolescents ( M age  = 12.5, 45.9% female, 21.9% immigrant), this study identified trajectories of problematic social media use (SMU) in parallel with trajectories of SMU frequency. Latent class growth analysis identified two subgroups with relatively high levels of problematic SMU over time: One showed high (24.7%) and one showed average SMU frequency (15.8%). Also, two subgroups with persistently low levels of problematic SMU were identified: One reported low (22.4%) and one reported high SMU frequency (37.1%). Although both subgroups with high levels of problematic SMU reported low subjective well‐being, the group with high SMU frequency showed low self‐control, whereas the group with average SMU frequency reported poor social competencies.